Risk Management Practices in Regional Public Hospitals: An Analysis of BLUD Financial Management in Accordance with Ministerial Regulations - Kristanto, Patricia Frenio; Lisdiono, Purwatiningsih (E-Jurnal Akuntansi; Vol 35 No 2 (2025)DO - 10.24843/EJA.2025.v35.i02.p08, 2025)
This study examines the implementation of risk management at W Regional General Hospital (RSUD W), which operates under the financial management model of a Regional Public Service Agency (BLUD). The evaluation is based on the integrated risk management guidelines set forth in Minister of Health Regulation (PERMENKES) No. 25 of 2019, complemented by the ISO 31000 risk management framework. Data were collected through semi-structured interviews with key stakeholders and a review of internal documentation, including the hospital’s profile, strategic and business plans, budget reports, and risk management documentation. A thematic analysis approach was employed to evaluate practices across the stages of risk management. The findings reveal that although the hospital has adopted an integrated risk management framework encompassing all prescribed stages, the implementation falls short of full compliance with the standards outlined in PERMENKES No. 25 of 2019. While certain processes align with regulatory expectations, the application of risk management remains inconsistent, particularly in non-clinical and financial functions. These discrepancies suggest a need for greater coherence and rigor in implementation. To enhance the effectiveness of risk management and improve hospital performance, the study recommends strengthening communication processes, conducting more robust and targeted risk analyses, and fostering a stronger organizational culture centered on risk awareness and accountability. These improvements are essential for achieving a more consistent and comprehensive application of integrated risk management within the hospital’s operational and financial framework. Keywords: BLUD; PERMENKES No. 25 of 2019; Regional Hospital, Risk Management; The Health Law No. 17 of 2023